2019
DOI: 10.1049/iet-rpg.2018.5917
|View full text |Cite
|
Sign up to set email alerts
|

Data‐driven wind speed forecasting using deep feature extraction and LSTM

Abstract: Wind speed forecasting is important for high-efficiency utilisation of wind energy and management of grid-connected power systems. Due to the noise, instability and irregularity of atmosphere system, the current models based on raw historical data have encountered many problems. In this study, a deep novel feature extraction approach is developed based on stacked denoising autoencoders and batch normalisation. Then the deep features extracted from raw historical data are fed to long short-term memory (LSTM) ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(40 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…The prediction method based on statistical theory has been widely used recently. Common statistical models include grey model (GM) [18], [19], autoregressive integrated moving average (ARIMA) [20], [21], support vector regression (SVR) [22], [23], multiple linear regression (MLR) [24], long-term and short-term memory network (LSTM) [9], [25], [26], artificial neural network(ANN) [27], machine learning algorithm(ML) [22], deep learning algorithm(DL) [29] and other hybrid models [30]. More and more researchers use machine learning methods to extract internal patterns from data.…”
Section: Introductionmentioning
confidence: 99%
“…The prediction method based on statistical theory has been widely used recently. Common statistical models include grey model (GM) [18], [19], autoregressive integrated moving average (ARIMA) [20], [21], support vector regression (SVR) [22], [23], multiple linear regression (MLR) [24], long-term and short-term memory network (LSTM) [9], [25], [26], artificial neural network(ANN) [27], machine learning algorithm(ML) [22], deep learning algorithm(DL) [29] and other hybrid models [30]. More and more researchers use machine learning methods to extract internal patterns from data.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, deep learning provides a systematic solution to handle big data problems, since deep learning models can take advantage of many samples to learn the hierarchical representations by combining the low-level input more effectively for big data with the characteristics of the large variety and large veracity. In a few recent publications, the results of deep learning have shown efficiency and greater accuracy in wind speed and wind power forecast problems [15][16][17][18]. Unfortunately, all these studies focused on the overall wind speed or wind power of a wind farm.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of wind power generation technology, the installed capacity and unit capacity of wind turbines are increasing constantly. Improving the service life of wind turbines and the wind energy utilisation is a research focus [1]. Studies have shown that accurate wind direction prediction can effectively improve the performance of wind turbine yaw system [2].…”
Section: Introductionmentioning
confidence: 99%